2010
DOI: 10.1055/s-0029-1246193
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Botulinum-A Toxin for the Treatment of Refractory Overactive Bladder in Children

Abstract: Intravesical BTX-A injection appears to be safe and useful in children presenting with idiopathic overactive drug-resistant bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 14 publications
2
14
2
2
Order By: Relevance
“…This is consistent with previous studies in children with OAB [11,12]. From our FBC functional bladder capacity a One female patient experienced personality changes and dry mucous membranes data, male patients had higher rates of both complete and partial success.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with previous studies in children with OAB [11,12]. From our FBC functional bladder capacity a One female patient experienced personality changes and dry mucous membranes data, male patients had higher rates of both complete and partial success.…”
Section: Discussionsupporting
confidence: 92%
“…This has been observed previously [11,12,14,15]. It is interesting that there was a significant improvement in nocturnal symptoms where they existed.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Only a small number of studies have reported the use of BTX-A in children with IDO, and only two have described more than 10 patients [27,28]. Hoebeke et al [27] utilized 100 U of onabotulinumtoxinA, and of 15 patients in the study, 3 were deemed not to have responded.…”
Section: Botulinum Toxin In Children With Idiopathic Detrusor Overactmentioning
confidence: 99%